Creating Sharia Capital Market Literation Strategy on Social Media among Young Moslem - Rosana Eri Puspita; Saifudin Saifudin (Department of Islamic Economics, Islamic University of Indonesia, 2020)
This study aims to create a sharia capital market literation strategy on social media among young Moslem based on influence from social media influencer, social presence, and trustworthiness. The approach taken in this research is quantitative. Data is collected with the help of research instruments in the form of online questionnaires. The population in this study is the young Moslem who tends to be a social media. The sample size in this study was113. The testing tool in this study used SPSS and a regression test was conducted to determine the effect of this research variable. The results show that social media influencers, social presence, and trustworthiness have a significant effect on intention-to- learn sharia capital markets. The study suggests many programs to create sharia capital market literation on social media among young Moslem.